2020
DOI: 10.9734/jpri/2020/v32i2530829
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Iron Nanoparticles Synthesized Using Dried Ginger

Abstract: Zingiber officinale (also called ginger) is commonly used for traditional treatment of various diseases and for culinary purposes. This plant species is a herbaceous and develops yearly pseudostems around one meter tall bearing limited leaf cutting edges. The synthesis of metal nanoparticles and nanocomposites is an emerging area of research and exploration in the field of material science for their unique size and shape and have reliant features that are different from the regular bulk structure. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Shenai et al in the year 2017 stated that the ethanolic leaf extract of Caralluma fimbriata is capable of reducing cell proliferation by inducing anticancer activity of COLO 320 cells when we compare with our study we found that 30 μg/ml can lead to apoptosis [23]. The activity of ginger extracts performed by different researchers found that the plant is with good pharmacological activity [24,25]. Jennifer et al have used KB cells to evaluate the anticancer activity with increasing concentrations of the ethanolic extract of C. fimbriata (100 -300µg/m1) and has shown a dose-dependent increase in anticancer activity in KB cell lines.…”
Section: Discussionsupporting
confidence: 70%
“…Shenai et al in the year 2017 stated that the ethanolic leaf extract of Caralluma fimbriata is capable of reducing cell proliferation by inducing anticancer activity of COLO 320 cells when we compare with our study we found that 30 μg/ml can lead to apoptosis [23]. The activity of ginger extracts performed by different researchers found that the plant is with good pharmacological activity [24,25]. Jennifer et al have used KB cells to evaluate the anticancer activity with increasing concentrations of the ethanolic extract of C. fimbriata (100 -300µg/m1) and has shown a dose-dependent increase in anticancer activity in KB cell lines.…”
Section: Discussionsupporting
confidence: 70%
“…Initially the iron nanoparticles were identified by stable dark brown colour and the surface plasmon resonance was at the peak positioned at 370 nm. Their study supported that dried ginger Zingiber are important sources for potent biologic activities and thus these plant-based nanoparticles may be essential in the treatment of various pathologic conditions [35,36]. The morphology of copper nanoparticles synthesized from the extract of Eclipta prostrata leaves as analysed by HRTEM shows spherical and agglomerated particles ranging from 28 to 45 nm [37].…”
Section: Resultsmentioning
confidence: 83%
“…The previous study involves the synthesis of selenium nanoparticles incorporating garlic oil. It can be deduced that garlic oil-mediated selenium nanoparticles have a good cytotoxicity activity at high concentrations [19]. In another study, the green synthesis of selenium nanoparticles was easy and simple.…”
Section: Introductionmentioning
confidence: 96%